Analisis Faktor Penyebab Waste Besi dan Mitigasi pada Proyek Toll KLBM (Krian Legundi Bunder Manyar) - Rizki, Muhammad Alvan; Mudjanarko, Sri Wiwoho; Abdulrahim, Muslimin (Jurnal Spesialis Teknik Sipil (JSpTS), 2025)
In general, iron material is a support of structural buildings. Waste iron material is waste that has a high enough value in a construction that is of particular concern in current construction projects. Iron waste material can be defined as material, which does not add value or progress to construction projects. So that more waste can make a loss project. Many factors cause iron material waste in the KLBM Toll project, both internal and external factors. The population of this research is the KLBM Toll Project. Research data obtained through the distribution of questionnaires and interviews with KLBM Toll construction practitioners using Google Form. Data taken from 11 respondents are probability, impact, and mitigation data. Data processing uses Fault Tree Analysis, Expected Monetary Value, and Mitigation Decision. The largest Expected Monetary Value results show the biggest factor causing iron material waste. The results showed the three biggest causes of iron material waste based on the EMV value were the construction had already taken place, the owner made a design change, the planner was less competent, and the iron material was lost / vandalism. The biggest cause category is in terms of design. Mitigation that can be done is to review the design and structural drawings with value engineering, improve communication in design planning, hold regular meetings between the owner and contractor, check material regularly, protect iron material properly for example installing fences in the area of iron stock, and provide additional security like cctv.